Analisis sifat fisika pemanfaatan pati tandan kosong sawit dan limbah plastik LDPE sebagai bahan pembuatan plastik biodegradabel - Hidayani, Tengku Rachmi; Pelita, Elda; Gusfiyesi, Gusfiyesi (Majalah Kulit, Karet, dan Plastik, 2017)
This research aimed to overcome the issue of plastic packaging waste that accumulates in nature because synthetic polymers cannot be easily unraveled by bacteria. Biodegradable plastics were produced by mixing waste of plastics of the low density polyethylene (LDPE) with starch of empty palm fruit bunches, modified with the addition of maleic anhydride as a crosslinking agent. To produce biodegradable plastics, different compositions of LDPE waste, starch of empty palm fruit bunch, maleic anhydride, and benzoyl peroxide were used, namely (90: 10: 1: 1), (80: 20: 1: 1), (70: 30: 1: 1), and (60: 40: 1: 1). Research stages consisted of extraction of starch from palm empty fruit bunch (PEFB); preparation of biodegradable plastic powder with the reflux method and xylene solvents; and making of biodegradable plastics using the press molding method. Based on the results of characterization, it was revealed that the optimum condition was generated by biodegradable plastics with the composition of LDPE waste, starch of empty palm bunches, maleic anhydride, and benzoyl peroxide was equal to 60: 40: 1: 1, which generated the tensile strength value of 6.9410 N/m2, the elongation at break of 3.1875%, the the melting point temperature of 103oC, and the decomposition temperature of 384oC. Besides, the thermal gravimetric test generated a residue of 12.6% and results of the analysis on morphological properties suggested that the starch distributed evenly.Keywords: Biodegradable plastics, LDPE waste, LDPE-g-MA, starch, palm empty fruit bunch.